Zn2+/Cd2+ optical discrimination by fluorescent acridine-based bis-macrocylic receptors. Issue 11 (2nd November 2017) - Aragoni, M. Carla; Arca, Massimiliano; Bencini, Andrea; Caltagirone, Claudia; Conti, Luca; Garau, Alessandra; Valtancoli, Barbara; Isaia, Francesco; Lippolis, Vito; Palomba, Francesco; Prodi, Luca; Zaccheroni, Nelsi
Abstract: A new acridine-based fluorescent chemosensor, L2, featuring two sulfurated macrocyclic units has been synthesised. Proton and metal binding properties ofL2 have been studied in H2 O/CH3 CN (1:1 v/v) by potentiometric and spectrophotometric measurements and compared with those of the analogous and previously published bis -macrocyclic receptor featuring two [9]aneN3 units (L1 ). Despite a thermodynamic selectivity observed for Zn 2+ with bothL1 andL2, L2 shows a marked sensing selectivity towards Cd 2+ via a chelation enhancement of fluorescence (CHEF) effect both in H2 O/CH3 CN (1:1 v/v) and in H2 O using silica core-PEG shell nanoparticles as vehiculant. On the other hand, L1 shows a selective optical sensing towards Zn 2+ in agreement with the thermodynamic selectivity observed for the same metal ion. Abstract :